Induced breeding of stinging catfish, Heteropneustes fossilis using Gonopro-fh in mini portable hatchery and extension education - Siangbud, J. Richwa-ika. Diah.; Siddiqui, Shadab; Vyas, Vipin (AG Volumes, 2025)
The present study focused on the induced breeding of Heteropneustes fossilis (stinging catfish) using the synthetic hormone Gonopro-FH in a mini portable hatchery setup, conducted between August and December 2023 at the Department of Zoology and Applied Aquaculture, Barkatullah University, Bhopal, Madhya Pradesh. A total of 20 healthy brooders were collected, acclimatized, and managed in hygienically prepared tanks. Broodstock were fed a supplementary diet rich in protein and micronutrients to promote gonadal development. The breeding system comprised a specially designed four-tank setup, with an elevated incubation tank facilitating a circular water flow pattern to mimic natural conditions and ensure proper oxygenation. The inner incubation chamber was equipped with a plankton net and vertical outlet for safe egg retention and water exchange. Induced breeding was initiated through intramuscular injections of Gonopro-fh at doses of 0.6 ml for females and 0.4 ml for males. After a latency period of eight hours, females were stripped of eggs, and testes from males were extracted. Fertilization was achieved through manual mixing with distilled water, and the fertilized eggs were incubated in the mini hatchery with continuous water flow. Additionally, as part of an extension education initiative, field demonstrations and training programs were conducted in Behrawal (Shajapur) and Berasia (Bhopal). These sessions aimed to transfer knowledge on induced breeding, hatchery management, and modern aquaculture techniques to rural farmers, enhancing local capacity for sustainable fish farming. This integrated approach not only demonstrated the effectiveness of portable hatchery systems for H. fossilis but also contributed to rural development and food security through skill enhancement and technology dissemination